GRADING DISCREPANCY IN GLOBAL EDUCATION - Dilon, Cell (PEOPLE: International Journal of Social Sciences, 2018)
This research paper explores the history, ideas and relevance of grading in the globalized world and discusses if grades are a proficient tool to measure proficiency in academic disciplines. It investigates finding based on a simple experiment, which shows grave differences in grading worldwide. The idea of grading was implemented in the eighteen century and this research explores if a system that is based on national measurement has relevance in the globalized world. This research examines the relationship between grades teachers give and proficiency scores given to the same students by external raters. This research found little comparison between teachers’ grading system and student proficiency. The research concludes that the current grading systems are of little to no use in the general measurement of proficiency of academic disciplines. It is the recommendation of the research that new measures are implemented and a new system not only based on proficiency skills are used to measure academic excellence.